Implementation of Traditional Fort Games as a Means of Developing Motor Skills in Elementary School Children - Yuda, Azmi Wira; Fachrezi, Figo; Rahmatullah, Muhammad Imam (Journal of Physical Education Innovation, 2024)
Motor development is an important aspect in the growth and development of elementary school age children. Physical education (PE) learning has a significant role in supporting students' motor development through structured and planned physical activity. The aim of this research is to examine the role of physical education learning on the motor development of elementary school students and identify effective learning strategies. The method used is a literature review approach by collecting and analyzing data from various relevant literature sources using content analysis techniques. The research results show that elementary school students' motor development can be maximized by maximizing student participation in physical education subjects that prioritize physical activity and healthy living training. The use of a commando teaching style in learning the game of rounders is also effective for developing students' basic motor skills. Physical education learning that involves physical activity and games can create a pleasant learning atmosphere, increase students' motivation and interest in learning, and provide benefits for health and social-emotional development. Therefore, in conclusion, effective physical education learning and paying attention to students' motoric development is very important to support optimal growth and development of elementary school students. Therefore, physical education teachers must design learning that suits the characteristics and needs of students' motor development, and use appropriate learning strategies to optimize their motor potential.